Phenotype of POLE-mutated endometrial cancer - Imboden, Sara (PLoS One, 2019)
BACKGROUND AND PURPOSE: Individualized therapy in endometrial cancer, the most common gynaecologic cancer in the developed world, focuses on identifying specific molecular subtypes. Mutations in the exonuclease domain of the DNA polymerase epsilon (POLE) gene define one such subtype, which causes an ultra-mutated tumour phenotype. These tumours may have an improved progression-free survival and may be receptive to specific therapies. However, the clinical phenotype of these tumours is unknown. The objective of this study was to evaluate the clinical and genetic features of POLE-mutated tumours from a large cohort of women whose cases are characterized by: (1) the availability of detailed clinical and lifestyle data; (2) mutation analysis; and (3) long-term follow-up. METHODS: A total of 604 patients with endometrial cancer were included in the study. Data from a detailed questionnaire, including lifestyle and family history information, provided extensive pertinent information on the patients. Sequencing of exons 9–14 of the POLE gene was performed. Follow-up data were gathered and analysed. RESULTS: Hotspot pathogenic POLE mutations were identified in N = 38/599 patients (6.3%). Patients with a POLE-mutated tumour were significantly younger, were more often nulliparous, and had a history of smoking. POLE-mutated tumours were more frequently aneuploid. Prognosis for patients with hotspot POLE-mutated tumours was significantly better in comparison with patients with non-mutated tumours; however careful selection of pathogenic mutations is essential to the definition of this prognostically favourable group. CONCLUSIONS: This study demonstrates that POLE-mutated endometrial cancer is significantly associated with previously unknown clinicopathologic characteristics. Outcome in POLE-mutated tumours was excellent in cases with hotspot mutations. Our results suggest that prediction of excellent outcome in cases of POLE-mutated EMCA should be restricted to cases of EMCA with hotspot mutations until further data are available on the rising number of mutations with unknown significance.